Strategi Dinas Perpustakaan Dan Kearsipan Provinsi Kepulauan Riau Dalam Meningkatkan Minat Baca Masyarakat - Sabirin Sabirin; Agus Hendrayady; Jamhur Poti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
problems with services such as collections, poor services, lack of facilities, and declining visits. The purpose of this research is to find out the strategy DPK Riau Islands in increasing people's interest in reading. This research uses descriptive qualitative research. Research results: (1) Time Dimension and Future Orientation The Time Dimension and Future Orientation, DPA Riau Islands implements strategies such as mobile libraries, library tours, socialization, the kacapuri application, and the OPAC system. (2) Internal and External Dimensions, strengths such as providing library cars, technology and digital facilities in attracting interest in reading. Weaknesses such as limited library car units, kacapuri application collections, and books that have not been recorded in OPAC. Opportunities and threats such as increasing and inhibiting knowledge in reading. (3) The dimension of utilization of sources, the allocation of funds comes from the APBD and APBN. Furthermore, facilities and infrastructure are adequate, although they need to be optimized. (4) Top Management Involvement Dimension, the head of service has conducted evaluation and supervision in the implementation of strategies and services provided. (5) Multi-field dimension, employees carry out procedures and are responsible for providing provincial library services.